Linear and whorled nevoid hypermelanosis associated with neurological manifestations. - Landeta-Sa, A.P.; Escandón-Pérez, S.; Comonfort-Palacios, V.; Cazarín-Barrientos, J.; Jaramillo-Manzur, S.C. (European Journal of Pediatric Dermatology, 2020)
Linear and whorled nevoid hypermelanosis (LWNH) is an extremely rare pigmentary mosaicism. It is characterized by hypermelanic macules that follow a Blaschko’s lines pattern. The disease has been found to be associated with the presence of trisomy 4, 7, 13, 14, 18, 20 and chromosome X-linked disorders involving mutations at the Xp21-p22 locus. However, LWNH usually presents as mosaicism. Only 16 to 31% of the cases are associated with neurological and cardiac disorders. Here is reported the case of a 6-year-old female patient with a history of generalized absence seizures and sleep disorders, that were associated with LWNH.